A scoping review protocol on diagnostic strategies to detect occult malignancies in individuals with ischemic stroke. - Jenneke Leentjens; Nicholas L J Chornenki; Janneke Spiegelenberg; Valentina Ly; Dariush Dowlatshahi; Deborah M Siegal (PLoS ONE)
Background Emerging data show an increased risk of ischemic stroke in patients with a new diagnosis of cancer. As the risk of stroke begins to increase 150 days before cancer is diagnosed, stroke may be the first clinical manifestation of undiagnosed cancer. About 6% of patients with cryptogenic ischemic stroke (unknown etiology after diagnostic evaluations) are diagnosed with cancer within one year. However, the optimal cancer screening strategy in this population is not known. We aim to conduct a scoping review of screening strategies for occult cancer in individuals with ischemic stroke. Methods Electronic databases including MEDLINE (Ovid), EMBASE (Ovid), CINAHL (EBSCOhost) and Scopus will be systematically searched to identify articles that report on screening strategies for occult cancer in individuals with ischemic stroke. At least two investigators will independently perform two-stage study selection consisting of title/abstract screening and full-text review, followed by data extraction. Thereafter, a thematic analysis will be conducted to provide an overview of what diagnostic tests/strategies have been used, and their clinical utility in terms of positive and negative predictive value (when available). Conclusion We anticipate that the findings of this scoping review will identify strategies used to detect occult cancer in individuals with ischemic stroke and summarize their clinical utility (if reported). Addressing this knowledge gap will help guide the development of future clinical trials on occult cancer screening patients with ischemic stroke.